Integrated landscape approaches in the tropics: A brief stock-take - Reed, J.; Ickowitz, A.; Chervier, C.; Djoudi, H.; Moombe, K.; Ros-Tonen, M.A.F.; Yanou, M.; Yuliani, L.; Sunderland, T.C.H. (Elsevier, 2020)
Continued overexploitation of natural resources and the associated impacts of climate change threaten the sustainability and biodiversity of our global social-ecological systems. ‘Integrated landscape approaches’ are governance strategies that attempt to reconcile multiple and conflicting land-use claims to harmonize the needs of people and the environment and establish more sustainable and equitable multi-functional landscapes. Such approaches have gained prominence in recent conservation and development discourse, but critics have suggested a need for evidence of effectiveness to bridge knowledge-implementation gaps. Here we review the recent literature to provide a brief update on developments in the science and practice of landscape approaches, primarily in the tropics. We show that despite considerable enthusiasm for landscape approaches, the evidence base within the scientific literature remains poorly developed. Future application of landscape approaches requires concerted transdisciplinary actions that connect scales of governance to address the complex political economies in contested tropical landscapes. We highlight important challenges and opportunities for landscape approach implementation, particularly related to bridging sectorial and disciplinary divides, engaging the private sector, and monitoring landscape performance.